Dust Storms - Hassn, S. A.; Jamil, A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study deals with the phenomena of dust storms in Iraq based on the data recorded by the Iraqi Organization for three stations which are: Mosul, Baghdad, and Nasiriyah.60  years was  the    period and  the  relation  between the  three stations data covered dust storms cases and the wind speed was also studied. The months and years which are mostly affected by dust storms during the period under consideration are presented, Finally Autocorrelation for three stations are founded.